The whole Bible story - Marty, William Henry (Minneapolis, Minn. : Bethany House, 2011)
"Bible College professor makes the stories of the Bible accessible by placing them in chronological order and simplifying the language"--Provided by publisher.
From creation to Babel -- Abraham, Isaac, Jacob, and his sons -- Moses and the Exodus -- Wandering in the wilderness -- The wilderness and the death of Moses -- The promised land -- The time of the judges -- The kingdom unites -- David and Solomon -- A kingdom divided : northern kingdom -- A kingdom divided : southern kingdom -- God's people in exile -- Birth and childhood of Jesus -- Jesus' early ministry -- Great Galilean ministry -- Later Judean ministry, Perean ministry, and journey to Jerusalem -- The crucifixion of Jesus -- Burial and resurrection -- The story of the church (Acts).
"Everything that happens in the Bible in plain English"--Cover.
Keywords: Bible stories, English